Relationship between Individual and Social Characteristics of Medical Students of Iran and Academic Failure: Systematic Review - Ali Akbar Haghdoost; Ali Akbar Haghdoost; Rezvan Ansari; Tahereh Changiz (Kerman University of Medical Sciences, 2016)
Background & Objective: Recognition of the causes and correlates of academic failure which is one of the failures of the education system is an important practical issue in education researches Despite the large number of studies in this field in Iran no comprehensive reviews of all published documents in this respect have been carried out Thus the aim of the present study was the systematic review of all texts published during the previous 15 years and determination of the role of individual personality and social factors related to academic failure of students Methods: In the present study documents were systematically reviewed and information gathered Articles which were related to the causes of academic failure of students of medical universities in Iran and published from March 1999 until February 2010 were studied Using census method 1008 articles were screened The full text of 26 articles with minimum quality of research was available Results: Based on the findings of the study male gender higher age of entry to college marriage mental and physical problems lack of interest in the field of education lower average score of school diploma or previous degree longer duration of time from diploma to university admission lack of studying during the term greater use of the internet and lack of scientific and research activities are individual factors that can lead to academic failure in students Based on the systematic review of literature the causes of academic failure of students were having a second job living in the dormitory and a nonempirical diploma Among familial and social factors low education level of father and mother financial problems family problems large number of family members poor social activity and being an extrovert were associated with academic failure Conclusion: Despite the many studies on the causes of academic failure it seems that the standards and definitions used in different studies vary Therefore to promote the quality of work standardization must be performed The views of faculty members were largely consistent with the facts found in the literature This showed that university teachers experiences in this regard are reliable  Moreover considering the major listed causes it seems that groups who are at higher risk of academic failure can be identified and preventive measures applied to them